The saprotrophic Pleurotus ostreatus species complex: late Eocene origin in East Asia, multiple dispersal, and complex speciation - Jing Li; Li-Hong Han; Xiao-Bin Liu; Zhi-Wei Zhao; Zhu L. Yang (IMA Fungus)
Abstract The Pleurotus ostreatus species complex is saprotrophic and of significant economic and ecological importance. However, species delimitation has long been problematic because of phenotypic plasticity and morphological stasis. In addition, the evolutionary history is poorly understood due to limited sampling and insufficient gene fragments employed for phylogenetic analyses. Comprehensive sampling from Asia, Europe, North and South America and Africa was used to run phylogenetic analyses of the P. ostreatus species complex based on 40 nuclear single-copy orthologous genes using maximum likelihood and Bayesian inference analyses. Here, we present a robust phylogeny of the P. ostreatus species complex, fully resolved from the deepest nodes to species level. The P. ostreatus species complex was strongly supported as monophyletic, and 20 phylogenetic species were recognized, with seven putatively new species. Data from our molecular clock analyses suggested that divergence of the genus Pleurotus probably occurred in the late Jurassic, while the most recent common ancestor of the P. ostreatus species complex diversified about 39 Ma in East Asia. Species of the P. ostreatus complex might migrate from the East Asia into North America across the North Atlantic Land Bridge or the Bering Land Bridge at different times during the late Oligocene, late Miocene and late Pliocene, and then diversified in the Old and New Worlds simultaneously through multiple dispersal and vicariance events. The dispersal from East Asia to South America in the middle Oligocene was probably achieved by a long-distance dispersal event. Intensification of aridity and climate cooling events in the late Miocene and Quaternary glacial cycling probably had a significant influence on diversification patterns of the complex. The disjunctions among East Asia, Europe, North America and Africa within Clade IIc are hypothesized to be a result of allopatric speciation. Substrate transitions to Apiaceae probably occurred no earlier than 6 Ma. Biogeographic analyses suggested that the global cooling of the late Eocene, intensification of aridity caused by rapid uplift of the QTP and retreat of the Tethys Sea in the late Miocene, climate cooling events in Quaternary glacial cycling, and substrate transitions have contributed jointly to diversification of the species complex.